The simple semi empirical dependences for turbulent shear stresses, kinetic energy of turbulence and the components of turbulent intensity for wall jet - Ищенко, С.А.; Бондарец, А.А. (Proceedings of National Aviation University, 2010)
The fluctuating components of velocity and their correlation for turbulent jets that spread in a moving stream on the smooth and roughness surfaces were investigated.